FORMATION OF THE STRATEGY OF BANKING INSTITUTIONS IN UKRAINE IN THE CONDITIONS OF THE FINANCIAL MARKET DIGITALIZATION AND MACROECONOMIC INSTABILITY - Sadchykova , I. V.; Kolotylo , L. L.; Volok , A. R. (The actual problems of regional economy development, 2024)
In the article, a brief historical overview of the emergence of the term “strategy” is provided, old and new approaches to the definition of the concept of strategy are applied, and stages of strategic formation of banking institutions in the global banking environment are presented. Modern scientific approaches to defining the concept of the strategy are highlighted. The author’s definition of the strategy of banking institutions in Ukraine is presented. The main components of the banking strategy, namely the general strategy, operational strategy and the strategy of separately defined strategic tasks, are presented, their role in the formation of the priorities of the banking strategic development is determined. The relationship between the strategy of banking institutions and the goals of the bank and the needs of economic agents is investigated. The categories of banking institutions that have started three stages of the digitalization development are identified, such as: Classic banking, Digital banking, Figital banking in the financial sector of Ukraine, and the stages of growth of digital technologies in the financial markets of Ukraine and the EU are graphically shown. In the article, the impact of digital technologies on the financial market of Ukraine is shown, and the components of digital support for financial transactions are identified, in particular, the main ones are robotization of digital assistants and creation of robotic speaker programs, cyber security systems for online payments, tokenization of transactions, processing of large amounts of customer data, introduction of cloud servicess, technologies of the paperless electronic signature, artificial intelligence, fog computing of financial flows, next generation digital mobile technologies with new data encryption principles. The digital technologies used in the formation of the strategy of banking institutions in Ukraine are grouped. The main levels of integration of banking institutions in Ukraine into the international financial system were also determined. The integration of the innovative digital financial products at different stages of strategic planning was analyzed. In the article, the influence of globalization processes on the formation of the strategy of banking institutions in Ukraine are studied, and the main processes of financial and economic integration between the world and domestic banks were identified.